Protocol development for an efficient digitization of palaeontological heritage: The case of Camp dels Ninots fossil site (Spain) - Adriana Linares-Martín; Bruno Gómez de Soler; Roy M. Farman; Elena Moreno-Ribas; Pablo Mateos Prieto; Marta Fontanals; Andrea Alías; Javier Sopesens; Hugues-Alexandre Blain; Gerard Campeny Vall-llosera (Geoheritage, 2026)

Body mass index and prognosis of infective endocarditis - Raquel Frías-García; Patricia Muñoz García; Marina Machado Vilchez; Gregorio Cuerpo Caballero; Raquel Rodríguez-García; M Ángeles Rodríguez-Esteban; M Carmen Fariñas-Álvarez; José M. Miró Meda; Andrea Gutiérrez Villanueva; Guillermo Ojeda-Burgos; Ane Josune Goikoetxea-Agirre; Marina Bernal Palacios; et al. (Infectious Diseases, 2025)

Pre- and post-drought conditions drive resilience of Pinus halepensis across its distribution range - Léa Veuillen; Bernard Prévosto; Raquel Alfaro-Sánchez; Vincent Badeau; Giovanna Battipaglia; Santiago Beguería; Felipe Bravo; Thomas Boivin; J. Julio Camarero; Katarina Čufar; Hendrik Davi; Martin De Luis; et al. (Agricultural and Forest Meteorology, 2023)

NEOTROPICAL FRESHWATER FISHES : A dataset of occurrence and abundance of freshwater fishes in the Neotropics - Lívia Helena Tonella; Renata Ruaro; Vanessa Salete Daga; Diego Azevedo Zoccal Garcia; Oscar Barroso Vitorino; Tatiana Lobato‐de Magalhães; Roberto Esser dos Reis; Fabio Di Dario; Ana Cristina Petry; Michael Maia Mincarone; Luciano Fogaça de Assis Montag; Paulo Santos Pompeu; et al. (Ecology, 2023)
The Neotropical region hosts 4225 freshwater fish species, ranking first among the world's most diverse regions for freshwater fishes. Our NEOTROPICAL FRESHWATER FISHES data set is the first to produce a large‐scale Neotropical freshwater fish inventory, covering the entire Neotropical region from Mexico and the Caribbean in the north to the southern limits in Argentina, Paraguay, Chile, and Uruguay. We compiled 185,787 distribution records, with unique georeferenced coordinates, for the 4225 species, represented by occurrence and abundance data. The number of species for the most numerous orders are as follows: Characiformes (1289), Siluriformes (1384), Cichliformes (354), Cyprinodontiformes (245), and Gymnotiformes (135). The most recorded species was the characid Astyanax fasciatus (4696 records). We registered 116,802 distribution records for native species, compared to 1802 distribution records for nonnative species. The main aim of the NEOTROPICAL FRESHWATER FISHES data set was to make these occurrence and abundance data accessible for international researchers to develop ecological and macroecological studies, from local to regional scales, with focal fish species, families, or orders. We anticipate that the NEOTROPICAL FRESHWATER FISHES data set will be valuable for studies on a wide range of ecological processes, such as trophic cascades, fishery pressure, the effects of habitat loss and fragmentation, and the impacts of species invasion and climate change. There are no copyright restrictions on the data, and please cite this data paper when using the data in publications.

High versus standard doses of corticosteroids in severe COVID-19: a retrospective cohort study - Enric Monreal; Susana Sainz de la Maza; Elena Natera-Villalba; Álvaro Beltrán-Corbellini; Fernando Rodríguez-Jorge; Jose Ignacio Fernández-Velasco; Paulette Walo-Delgado; Alfonso Muriel; Javier Zamora; Araceli Alonso-Canovas; Jesús Fortún; Luis Manzano; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2021)